2016
DOI: 10.1164/rccm.201506-1100oc
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Bacteria, Virus, and Malaria Distinguish the Etiology of Pediatric Clinical Pneumonia

Abstract: Rationale: Plasma-detectable biomarkers that rapidly and accurately diagnose bacterial infections in children with suspected pneumonia could reduce the morbidity of respiratory disease and decrease the unnecessary use of antibiotic therapy.Objectives: Using 56 markers measured in a multiplexed immunoassay, we sought to identify proteins and protein combinations that could discriminate bacterial from viral or malarial diagnoses. Methods:We selected 80 patients with clinically diagnosed pneumonia (as defined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 53 publications
0
52
0
Order By: Relevance
“…Procalcitonin has been studied extensively in the setting of sepsis diagnosis but cannot distinguish between noninfected individuals and those with viral infections (58). Protein-panel assays have been shown to discriminate bacterial from viral infections but cannot discriminate patients with noninfectious inflammation (59, 60). Thus, all of these classifiers have certain strengths and weaknesses that will become more apparent with further prospective testing and direct comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Procalcitonin has been studied extensively in the setting of sepsis diagnosis but cannot distinguish between noninfected individuals and those with viral infections (58). Protein-panel assays have been shown to discriminate bacterial from viral infections but cannot discriminate patients with noninfectious inflammation (59, 60). Thus, all of these classifiers have certain strengths and weaknesses that will become more apparent with further prospective testing and direct comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Host-response biomarkers, such as C-reactive protein, interleukin(IL)-6, and procalcitonin, have been increasingly used to assist the diagnosis of a variety of infectious diseases, including pneumonia and sepsis. [66][67][68][69][70][71] A meta-analysis of 6708 adults with acute respiratory infection found that the use of procalcitonin to guide therapy was associated with a 17% reduced risk of mortality and a 2·4-day reduction in antibiotic exposure compared with controls, without increasing adverse outcomes. 72 However, data in children are scarce, and early studies have conflicting results.…”
Section: Host-response Biomarker Testingmentioning
confidence: 99%
“…77 Few studies in low-income and middle-income countries have investigated the consistency of hostresponse biomarkers in childhood pneumonia diagnoses. 68,69,78,79 Certain conditions complicate the definition of an optimal threshold of host-response biomarkers for diagnosis. For example, not all bacterial infections cause host-response biomarkers to rise, or to rise to the same degree.…”
Section: Host-response Biomarker Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…[122][123][124][125][126][127][128][129] Several other biomarkers, including the combination of haptoglobin, tumor necrosis factor (TNF) receptor 2, or interleukin 10, and tissue inhibitor of metalloproteinases 1, 130 have shown promise for the classification of children with bacterial pneumonia but require further evaluation.…”
Section: Bloodmentioning
confidence: 99%